EXPLORING NGOS’ PERSPECTIVES AND THEIR ROLE IN EDUCATION REFORM IN EGYPT - Moriatis, Ioanna (AUC Knowledge Fountain, 2024)
This exploratory study elicits NGO perceptions regarding Egypt’s Ministry of Education and Technical Education’s (MOETE) reform efforts, their interest in participating in education reform and policy advocacy, and their existing relationship with the ministry. Drawing on the findings from semi-structured, in-depth interviews with 13 representatives of education NGOs based in Cairo and Giza, this thesis takes a qualitative approach toward answering the following research question: How do NGOs targeting K-12 youth perceive their role in shaping education reform in Egypt? Despite having to navigate a host of obstacles to accessing public schools and working with the MOETE, the NGOs represented in this study have demonstrated that they are trying to leverage various strategies to target public school beneficiaries and create impact, both showcasing their dedication to creating change in the education sector and the wide reach they have in the community. Ultimately, this thesis highlights the persistent system of centralization and restrictions under which many education NGOs continue to operate and the potential for the MOETE to look increasingly to the civil society sector for guidance on public opinion, feedback and monitoring support with regard to reform rollouts, and ideas and innovative models.